Mortality in children and adolescents in Western Democratic Republic of Congo: retrospective analysis of verbal autopsy and demographic data from the Kimpese Health and Demographic Surveillance System - Carina King; Tobias Alfvén; Helena Hildenwall; Mala Ali Mapatano; Joël Kiniati Fumwakwau; Mattias Schedwin; Mireille Amba Ngale; Delphin Mavinga Phanzu (BMJ Paediatrics Open)
Background There is a paucity of data on causes of death in children and adolescents that can be used for public health prioritisation in settings with the highest mortality burden. We aimed to estimate the causes and circumstances around deaths for the age group 1 month to 19 years in the Western Democratic Republic of Congo.Methods Analysis of verbal autopsy and demographic data from the Kimpese Health and Demographic Surveillance System (rural setting 200 km west of Kinshasa) was collected between September 2018 and September 2021. About 66 000 individuals were surveyed yearly using structured questionnaires. Vital events were registered and identified deaths followed up with the World Health Organization 2012 or 2016 verbal autopsy questionnaire. Verbal autopsies were analysed using the InterVA-5 algorithm to generate cause of death and circumstances of mortality categories at the population level. Individual and household characteristics relevant to child survival were compared between deceased and surviving individuals using Fisher’s exact test.Results Overall, 166/273 (61%) of identified deaths had a complete verbal autopsy. 74% of deaths occurred in children 1–59 months of age, and 70% of all deaths were classified as due to infectious diseases. The top three causes were malaria (35%), lower respiratory infection (12%) and diarrhoeal disease (9%). 78% of deaths occurred at home, and <5% were considered inevitable. However, 70% of individuals sought healthcare in the days preceding death. Recognition (39%), emergencies (27%) and accessing care (20%) were the main contributing categories to fatal outcomes. Characteristics had low coverage (32–72% for the first dose of vaccinations and <10% for water, sanitation and hygiene).Conclusions Results suggest a need to sensitise caregivers about care-seeking, home treatment and danger signs and improve access to health facilities, combined with improving the quality of care in facilities. Improvements in access to safe water, sanitation and vaccination coverage are also needed.